Control for EESS in Three-Phase Microgrids under Time-Domain Reference Frame via PBC Theory (2019)
This brief presents a general form of designing passivity-based controllers for electrical energy storage systems (EESS) in three-phase microgrids (TP-MGs) under time-domain reference frame. The control strategy proposed in this brief use the Clark's transformation known as αβ reference frame, avoiding to use phase-locked loop systems, which allows improving the dynamical performance in the energy storage devices. Passivity-based control guarantees stable operating conditions in the sense of Lyapunov for each EESS for different grid operation scenarios in the TP-MG. The design of the controllers is made by using passivity-based control (PBC) theory in conjunction to the dynamics of the error approach. A comparison to classical proportional-integral control method is used to show the applicability of the PBC approach presented in this brief. Simulation results are conducted via MATLAB/Simulink software. © 2004-2012 IEEE.